The Theoretical Analysis of the Role of Accounting in Achieving Good Governance in the Public Sector - Sri Wahyuni; Isra Maulina (EKSYA : Jurnal Ekonomi Syariah, 2025)
Good governance is an essential concept in the public sector that emphasizes transparency, accountability, efficiency, effectiveness, and public participation. Accounting plays a central role in providing reliable information as the basis for accountability and decision-making. This article aims to analyze the role of accounting in promoting good governance through literature review and a normative-critical approach. The study adopts a library research method by exploring the contributions of theories such as Agency, Legitimacy, Institutional, Stewardship, and Systems Theory to the practice of public sector accounting. The findings indicate that accounting is not merely a technical reporting tool, but also serves as an instrument of legitimacy, social control, and a driver of accountability culture. Strengthening human resource capacity, bureaucratic reform, and the implementation of information technology are critical factors in optimizing the function of accounting to support good governance in the public sector.